Association Between Quantitatively Measured Infrapatellar Fat Pad High Signal‐Intensity Alteration and Magnetic Resonance Imaging–Assessed Progression of Knee Osteoarthritis. Issue 5 (25th April 2019) - Han, Weiyu; Aitken, Dawn; Zheng, Shuang; Wluka, Anita E.; Zhu, Zhaohua; Blizzard, Leigh; Winzenberg, Tania; Cicuttini, Flavia; Jones, Graeme; Ding, Changhai
Abstract : Objective: To describe the cross‐sectional and longitudinal associations between quantitative measures of infrapatellar fat pad (IPFP) signal‐intensity alteration and knee structural abnormalities in patients with symptomatic knee osteoarthritis (OA). Methods: A total of 261 patients (mean ± SD age 63.0 ± 7.2 years) with symptomatic knee OA were selected from a randomized controlled trial with a follow‐up of 2 years. IPFP signal‐intensity alterations at baseline were quantitatively measured on T2‐weighted fat‐saturated magnetic resonance imaging using MATLAB. These quantitative measures included the SD of whole IPFP signal intensity measurement, the upper quartile value of high signal intensity (UQ H ), the ratio of volume of high signal‐intensity alteration to volume of whole IPFP (percentage H ), and the clustering effect of high signal intensity (clustering‐factor H ). Cartilage volume and defects and bone marrow lesions (BMLs) were assessed using validated measures. Results: Higher baseline SD of the IPFP, UQ H, and clustering‐factor H were associated with greater loss of tibial cartilage volume and larger increases in tibiofemoral cartilage defects over 2 years. Patients with high and medium tertiles of clustering‐factor H had greater loss of cartilage volume per annum compared with those with a low tertile (for high 4.9%, for medium 4.6%, and for low 3.3% annually). Baseline percentage H and clustering‐factor H were positively and significantly associated with increases in tibiofemoral BMLs over 2 years. Cross‐sectional associations between IPFP measures and knee structures were similar but more consistent. Conclusion: Quantitative measures of increased signal intensity in the IPFP were associated with knee structural abnormalities in the tibiofemoral compartment, suggesting that these measurements could be used as an additional entry criterion to enrich studies for faster progressors of knee OA.